Is there a relation between plantar fasciitis and total cholesterol levels? - Çatal, Bilgehan; Genç, Erdinç; Çaçan, Mehmet Akif; Güleryüz, Yiğit; Erdil, Mehmet Emin (Elsevier, 2022)
Background: The main objective of this study is to investigate the relationship between hypercholesterolemia and Plantar Fasciitis (PF). Methods: The study includes patients who presented to the orthopedics outpatient clinic with heel pain and were diagnosed with PF. The control group was composed of patients who came to the orthopedics outpatient clinic, with complaints other than heel pain. The two groups were compared in terms of epidemiological data, total cholesterol (TC) levels, and hypercholesterolemia prevalence. We also performed an in-group analysis of PF patients in terms of age, sex, body mass index, and duration of symptoms. Results: There were 238 patients (mean age, 46.7) in the PF group and 240 patients (mean age, 47.9) in the control group. There was a significant difference between the PF group and the control group in TC levels (207.6 +/- 47.5 versus 195.1 +/- 30.1, p = 0.001). Hypercholesterolemia (TC level > 240 mg/dL) was found in 22.7% (n = 54) of the patients in the PF group whereas in the control group this rate was 10.8% (n = 26) (p < 0.001). It was seen that the TC levels were significantly higher in patients over the age of 45 in the PF group (p = 0.038). We also found that TC levels were higher in PF patients with symptoms for longer than a year (p = 0.026). Conclusion: Significantly higher TC levels were found in PF patients in comparison with other orthopedic outpatients. Besides, being over the age of 45 and having a duration of symptoms longer than a year is associated with higher cholesterol levels for PF patients.
Keywords: Cholesterol; Heel Pain; Hypercholesterolemia; Hyperlipidemia; Plantar Fasciitis